Enhancing Security of MANETs by Implementing Elliptical Curve based Threshold Cryptography (International Journal of Engineering and Computer Science, 2018)
Mobile Ad-hoc Networks or MANETs is a prominent technique in wireless networks which is receiving a great attention by different groups . A Mobile Ad-hoc network is a group of wireless mobiles nodes that tends to form a network without any fixed infrastructure having mobile and self-configuring nodes. Security in MANETs is a challenging issue hence it requires efficient security scheme to protect itself against malicious attacks and interceptions. Elliptical curve based threshold cryptography provides a promising solution to enhance the security of MANETs than other existing popular algorithms such as RSA. In this paper we have discussed the implementation of Elliptic Curve Cryptography (ECC) based threshold cryptography(ECC-TC) using GNU Multi precision Library (GMP) and discussed their advantages for employment in MANETs to counter its security issues.